“This dog means Life”: making interspecies relations at an assistance dog agency. - Edminster, Avigdor (My University, 2011)
My ethnographic informants at an assistance dog agency say that dogs and humans can read each others' minds, have saved each others' lives, hear for one another, and are family and business partners. These clients, assistance dogs, staff, and volunteers have uniquely intimate, interdependent interspecies relationships despite the power of absolutist distinctions between humans and other animals. I explore how my informants understand and create shared and unshared dimensions between them as they also navigate and change ideas about the family, workplace, and larger society. Explored in tandem these relationships and cultural domains illuminate the anxieties, ambiguities, and securities experienced in both. Central to this project are the ways that shared embodied relational meaning emerges as my informants make meaningful lives together.
University of Minnesota Ph.D. dissertation. May 2011. Major: Anthropology. Advisor: Stuart McLean. 1 computer file (PDF); iv, 230 pages.
Keywords: Dogs; Embodiment; Interspecies; Kinship; Relational; Anthropology